2019
DOI: 10.3390/molecules24071278
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Influence of Steric Hindrance on Selective Anion Transport

Abstract: A series of symmetrical and unsymmetrical alkyl tren based tris-thiourea anion transporters were synthesised and their anion binding and transport properties studied. Overall, increasing the steric bulk of the substituents resulted in improved chloride binding and transport abilities. Including a macrocycle in the scaffold enhanced the selectivity of chloride transport in the presence of fatty acids, by reducing the undesired H+ flux facilitated by fatty acid flip-flop. This study demonstrates the benefit of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…It was shown that synthesized multicyclophanes are capable of forming stable supramolecular associates [20,21] and also can participate in oxidative polymerization reactions with supramolecular assistance [23]. TREN as a convenient platform for the design of anion receptors and sensors [24,25] has been chosen as a core of the synthesized multicyclophane. Pillararenes can effectively interact with phenazines, e.g., percarboxylated pillar[6]arene can form an inclusion complex with methylene blue in water with a high association constant [26].…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that synthesized multicyclophanes are capable of forming stable supramolecular associates [20,21] and also can participate in oxidative polymerization reactions with supramolecular assistance [23]. TREN as a convenient platform for the design of anion receptors and sensors [24,25] has been chosen as a core of the synthesized multicyclophane. Pillararenes can effectively interact with phenazines, e.g., percarboxylated pillar[6]arene can form an inclusion complex with methylene blue in water with a high association constant [26].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Matile's, [22][23][24][25][26][27] Talukdar's, [28][29][30][31][32] and Ballester's 22,33 research groups have used EYPC from Avanti Polar Lipids, while Chen [34][35][36][37][38] and Manna 39,40 have also used EYPC but purchased from Sigma-Aldrich. On the other hand, the Gale, 15,18,21,[41][42][43][44] and Quesada 45, As indicated before, when it comes to choosing the appropriate lipid to conduct transport assays, the decision should be made by considering, among other factors, the biological membranes to be mimicked. In this respect, EYPC is usually selected because it can emulate mammalian phospholipid composition.…”
Section: Lipidsmentioning
confidence: 99%
“…Usually, both are made up of NaCl (100 mM), but it is not uncommon to find works in the literature where M is Li + , Na + , K + , Rb + , Cs + or NMDG + and X is F -, Cl -, Br -, I -, NO3 -, AcO -, SCNor ClO4 -. 15,31,43,45 The intra-and extravesicular media composition may be dissimilar depending on the purpose of the experiment (pH, anion or dual gradient assay); however, regardless of the composition, the total ionic strength of both solutions must remain constant throughout a typical experiment.…”
Section: The Saltsmentioning
confidence: 99%
“…For instance, Matile's, [21][22][23][24][25][26] Talukdar's, [27][28][29][30][31] and Ballester's 21,32 research groups have used EYPC from Avanti Polar Lipids, while Chen [33][34][35][36][37] and Manna [38][39] have also used EYPC but purchased from Sigma-Aldrich. On the other hand, the Gale, 14,17,20,[40][41][42][43] As indicated before, when it comes to choosing the appropriate lipid to conduct transport assays, the decision should be made by considering, among other factors, the biological membranes to be mimicked. In this respect, EYPC is usually selected because it can emulate mammalian phospholipid composition.…”
Section: Lipidsmentioning
confidence: 99%